STRATEGI PENGEMBANGAN USAHATANI KEDELAI DI KABUPATEN GROBOGAN DENGAN PENDEKATAN ANALYSIS HIERARCHY PROCESS (AHP) - Avi Budi Setiawan; Fafurida Fafurida (Jurnal Ilmu Ekonomi dan Pembangunan, 2014)
Soybean is one of the agricultural commodity Grobogan. Soybean commodity is widely cultivated by farmers because the topography is consistent with the characteristics of the soil in Grobogan. In 2010 soybean production Grobogan is most widely in Central Java. However, Indonesia is still dependent on imported soybeans, especially in times of shortages of soybeans. This is partly also due to soybean production in soybean-producing region is very volatile while soybean demand in the market tends to increase. So, we need a strategy development of soybean farming in Grobogan. The goals to be achieved from the preparation of this study was to analyze the condition of soybean farming in Grobogan and obtain soybean farming development strategy in Grobogan based approach Analysis of Hierarchy Process. Alternative measures a priority to develop soybean are: Provision of continuous production factors and affordable, production factor subsidies, assistance to farmers, extension and education on effective post-harvest handling, Counseling institutional strengthening of farmer groups, and technical assistance (equipment, factors of production, training) to farmers. sedagkan least priority are: Incentives for active farmer organizations, cooperatives Revitalization and extension services and farmer partnerships with major employersKeywords: Soybean, Analysis of Hierarchy Process